Personality traits and gender differences in the development of attitude towards inter-ethnic issues among middle youth. - Idris, Fazilah; Hamzah, Azimi; Mastor, Khairul Anwar; Tamam, Ezhar; Wong, Su Luan; Suradi, Nur Riza (2007)
This paper reports preliminary findings on the middle youth's differences of personality traits among different ethnic, as well as the differences between gender, and the relationships between middle youth's personality traits and their attitude towards inter-ethnic issues. As many as 563 secondary school students in Selangor, representing middle youth, were sampled in this study. Instruments used were the Malay translated NED PI-R Personality Inventory (Mastor et aI., 2000) and a self-designed questionnaire on the attitude towards inter-ethnic issues. Results indicated that the Neuroticism, Extraversion, Agreeableness and Conscientiousness domains of personality traits were significantly different among the Malay, Chinese and Indian middle youth. In general, all ethnic possess average level of all domains of personality traits. Most importantly, it was found that personality trait domains of Extraversion, Openness, Agreeableness and Conscientiousness in middle youth were positively related to their attitude towards inter-ethnic issues.